A NOTE ON TOPOLOGICAL TRANSITIVITY OF THE NON-WANDERING SET AND THE CHAIN RECURRENT SET - Shoptrajanov, Martin (Matematichki Bilten, 2022)
In this paper we shall use the fundamental theorem of dynamical systems to improve some of the results from [5] concerning topological transitivity of the non-wandering set \(Ω(φ)\) and the chain recurrent set \(\mathcal{CR}(φ)\) in compact metric spaces.